Les marginalisés sur les marges: Les caractéristiques générales des volontaires espagnols dans l’armée française pendant la guerre d’Indochine - Bába, Viktória (Études sur la Région Méditerranéenne, 2023)
The Spanish military participation in the French army during the Indochina War (1946– 1954) is relatively unknown, but the destiny of the Spanish participants stays even more in the dark. One of our purposes, in this paper, is to uncover these potholes in Franco-Spanish historiography, thus starting with the explanation of the background of the French presence in the Indochinese Federation. In order to understand the reason why Spanish volunteers served in the French Foreign Legion, we shall examine their situation during the first decades of the twentieth century, and more specifically, during the government of Francisco Franco. Thus, the main objective of our paper is to study, with the help of the French military platform, Mémoire des hommes, the Spanish republicans on the run from the fascist regime, who sacrificed their lives in faithful service to France during the Anti-French Resistance War.